Application of electron beam melting method for recycling of tantalum scrap - Katia Vutova; Vladislava Stefanova; Peter Iliev (Materials Research Express, 2024)
The paper presents a study on the refining efficiency of tantalum scrap when applying the electron beam melting method to recycle tantalum material. Thermodynamic analysis and experimental tests were carried out at different technological regimes to determine the optimal conditions for obtaining tantalum with high purity. The behavior of the controlled impurities (W, Nb, Mn, Ce, Cr, Mo, Al, Fe, etc) and the influence of the thermodynamic and kinetic technological parameters (temperature, melting time) on the refining efficiency of the studied material were investigated. At a temperature of 3700 K and a melting time of 10 min, the highest overall degree of refinement of 98.82% and the highest tantalum purity of 99.987% were achieved.